Solar Power System Plaing & Design Resource Assessment, Site Evaluation, System Design, Production Forecasting and Feasibility Studies - Choi, Yosoon (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Photovoltaic (PV) and concentrated solar power (CSP) systems for the conversion of solar energy into electricity are technologically robust, scalable, and geographically dispersed, and they possess enormous potential as sustainable energy sources. Systematic planning and design considering various factors and constraints are necessary for the successful deployment of PV and CSP systems. This book on solar power system planning and design includes 14 publications from esteemed research groups worldwide. The research and review papers in this Special Issue fall within the following broad categories: resource assessments, site evaluations, system design, performance assessments, and feasibility studies.